Influence of Emergency Braking on Changes of the Axle Load of Vehicles Transporting Solid Bulk Substrates. (2017) - Vrabel, Jan; Jagelcak, Juraj; Zamecnik, Jan; Caban, Jacek
Abstract: When flowable solid bulk commodities are transported, their distribution in a vehicle cargo space may change due to a dynamic load, mainly due to intensive braking. This cargo movement causes changes of a load of particular vehicle axles, what may result in overloading of axles mainly in a front part of vehicle/combination, although the vehicle/combination was loaded correctly. This article quantifies the influence of intensive braking on axle load changes during a transport of cement and selected types of gravel. It is based on practical braking tests which were done for purposes of the quantification of this influence.